2017
DOI: 10.2134/jeq2016.07.0253
|View full text |Cite
|
Sign up to set email alerts
|

Stable Isotopes Reveal Rapid Cycling of Soil Nitrogen after Manure Application

Abstract: Understanding the fate of applied nitrogen (N) in agricultural soils is important for agronomic, environmental, and human health reasons, but it is methodologically difficult to study at the field scale. Natural abundance stable isotope measurements (δN) were used in this field study with micrometeorological measurements of nitrous oxide (NO) emissions to identify the biogeochemical processes responsible for rapid N transformations immediately after application of liquid dairy manure. Fifteen samplings occurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 81 publications
(156 reference statements)
2
13
0
Order By: Relevance
“…Therefore, the 8–20‰ differences in δ 15 N‐NO x between injected no‐till and broadcast without tillage are likely associated with different rates of NO production via nitrification and NO consumption. This association with nitrification is generally consistent with Snider et al (), who reported 56% of NH 4 + applied via liquid dairy manure application (broadcast with incorporation) in silt loam soil was lost after 3 days via NH 3 volatilization and 95% of the remaining NH 4 + was nitrified within 3 weeks.…”
Section: Resultssupporting
confidence: 89%
“…Therefore, the 8–20‰ differences in δ 15 N‐NO x between injected no‐till and broadcast without tillage are likely associated with different rates of NO production via nitrification and NO consumption. This association with nitrification is generally consistent with Snider et al (), who reported 56% of NH 4 + applied via liquid dairy manure application (broadcast with incorporation) in silt loam soil was lost after 3 days via NH 3 volatilization and 95% of the remaining NH 4 + was nitrified within 3 weeks.…”
Section: Resultssupporting
confidence: 89%
“…NO 3 is negatively charged, so it is not retained by the soil particles (Martius, Rudenko, Lamers, & Vlek, ) like other nutrients, such as ammonium (NH 4 ). Heterotrophic microbiological activity occurs during snowmelt (Brooks, Williams, & Schmidt, ; Clark, Chantigny, Angers, Rochette, & Parent, ), but has also been observed in snow‐covered soils during winter (Brooks et al, ; Clark et al, ; Pellerin et al, ; Sebestyen et al, ; Snider, Wagner‐Riddle, & Spoelstra, ). Net mineralization and nitrification may occur in frozen soils before snowmelt (Brooks et al, ; Clark et al, ), therefore presenting a risk of NO 3 net gains between fall and spring, particularly in the presence of organic amendments and in fine‐textured soils (Clark et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…This has implications for runoff‐soil interactions with possible anticipation of the timing of the first and major surficial soil NO 3 flush. As the water moves downstream, runoff NO 3 concentrations tend to decrease due to biological assimilation and denitrification, even in agricultural areas (Snider et al, ). However, at the spatial scales of nutrient release and mobilization (i.e., field‐scales), the spatial distribution of snow mass and melt rate are critical determinants of the spatial and temporal dynamics of NO 3 export.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, most studies on δ N focused on processes within the uppermost 10 cm of soil (Wang et al 2014;Snider et al 2017). Depth-related distributions were studied only in the upper 30 cm by Kerley and Jarvis (1997).…”
Section: Spatial Distribution Of δ Nmentioning
confidence: 99%